Pediatric Dental Management of an Uncommon Case of Mucopolysaccharidosis Type IV A (Morquio A Syndrome): A Case Report of a Three-Year Follow-Up - Andrea Gómez-González; Miguel Ángel Rosales-Berber; Paola De Ávila-Rojas; Amaury Pozos-Guillén; Arturo Garrocho-Rangel (Hindawi Limited, 2020)
Mucopolysaccharidosis type IV A or Morquio syndrome is an uncommon inherited metabolic condition caused by the deficient intralysosomal storage of glycosaminoglycans. Diagnosis is typically based on clinical examination, skeletal radiographs, and histochemical tests in blood cells or fibroblasts. It is characterized by evident skeletal deformities, poor joint mobility, severe growth deficit, occlusal anomalies, and enamel defects. The aim of the present clinical case report is to describe the general oral management provided to a 6-year-old female patient and its corresponding evolution for more than three years.